2017
DOI: 10.1177/0956462417725638
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of recreational drug use reported by men who have sex with men attending sexual health clinics in Manchester, UK

Abstract: Recreational drug use (RDU) has been reported to be disproportionately higher in men who have sex with men (MSM) when compared to their heterosexual counterparts. To identify RDU, links to risky sexual practices and infections for MSM attending three sexual health clinics across Manchester, United Kingdom, a retrospective case note review was conducted using a random powered sample of service users attending three sites during 2014. Three hundred and fifty-seven case notes were reviewed across three sites. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Binge drinking and tobacco and substance use were high in the study population, compared with the general population [ 74 ], which is consistent with previous reports [ 75 , 76 ]. In an online survey among MSM through Facebook in seven countries, including Brazil, it was observed that social networks and minority stressors can have significant effects on drug use and sex while drunk or high [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…Binge drinking and tobacco and substance use were high in the study population, compared with the general population [ 74 ], which is consistent with previous reports [ 75 , 76 ]. In an online survey among MSM through Facebook in seven countries, including Brazil, it was observed that social networks and minority stressors can have significant effects on drug use and sex while drunk or high [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…This bio-behavioural study of MSM in London found high rates of behaviours associated with increased risk of HIV transmission. Most men (60.1%) reported condomless sex in the last 3 months; most (59.3%) had had condomless sex with at least one casual partner in the previous 12 months; one in five reported having an STI in the previous 12 months; and one in five men reported chemsex in the last year, higher than most estimates observed in other studies [16-19]. Despite this, the number of new diagnoses in MSM in London is falling and according to estimates from surveillance data, rates of undiagnosed infection have decreased from 18% in 2013 to 10% in 2016 [5,20].…”
Section: Discussionmentioning
confidence: 61%
“… MSM: men who have sex with men; GHB/GBL: gamma-hydroxybutyric acid/gamma-butyrolactone. a Other drugs include rush, 94 khat, 66 opium, 66 morphine, 66 triazolam, 61 ethyl chloride, 77 flunitrazepam, 43 heroin, 31,34,41,60,61,63,66,75 phencyclidine(PCP), 32,61 legal highs, 77 ching, 77 methoxetamine, 77 ‘pills’, 77 anabolic steroids, 66,77 hallucinogens, 11,34,61,66,75,97 speed, 72 tranquilisers, 59 codeine compound, 14,61,66 tramadol, 24 nasally administered drug 34,98 and rohypnol. 11 …”
Section: Resultsmentioning
confidence: 99%